Tiruvaḷḷuvar aruḷiceyta Tirukkuṟaḷ antāti : mūlamum uraiyum - Araṅkacāmi, R. K. (SAMP early 20th-century Indian books project ;, 1946)
Commentary on selections from Tirukkuṟaḷ, ancient Tamil didactic poetry, by Tiruvaḷḷuvar; includes original text.